PREDIKSI PENURUNAN KUALITAS UAP PEMBANGKIT LISTRIK TENAGA GEOTERMAL DIHUBUNGKAN DENGAN STRATEGI PEMELIHARAAN DIMASA YANG AKAN DATANG - Mulyana, Cukup; Nurhilal, Otong; H Saad, Aswad; Taufik, Ahmad (BERKALA FISIKA, 2014)
In Geothermal power plant steam quality plays a very important role because it is associated with enthalpy and affects the reliability of the turbine. Studies have been carried out on the trend of a decrease in pressure, temperature and flow that comes out of a wellhead for 25 years. In addition the study also conducted in steam pressure drop duriing transmission process in the pipeline from the wellhead to the turbine due to friction factor , elevation , and junctions. Existing wellhead temperature is 202OC – 243OC, pressure of 8.2 kg/cm2 – 12.7kg/cm2. Operating parameters of the turbine are minimum pressure of 6.5 kg/cm2 and superheat temperature of 169oC. By looking at the trend of decrease in pressure and temperature, in the next few years is concerned to be achieved under the limit pressure. Concerning the decrease of enthalpy, give impact to decreasing of KWh. Therefore it should be anticipated from the beginning so it is not threat the continuity of the operation of geothermal power. From the study enthalpy did not decrease significantly in other hand the pressure drop significantly at the wellhead. The steam quality is still in good because the steam is superheated condition. The problem that needs to be addressed is the pressure drop from the wellhead to the turbine at 16.1 %. It is recommended to replace the T junction into a Y junction in order to minimize the pressure drop in the pipeline transmission. Keywords : steam quality, pressure, temperature, wellhead